Parents and Teachers System for Sekolah Kebangsaan Parit Raja - Md Siam, Muhammad Zulhilmi; Zainal, Nurezayana (Applied Information Technology And Computer Science, 2023)
This study focuses on implementing technology in managing the learning and teaching activities of Sekolah Kebangsaan Parit Raja in Batu Pahat. The current manual record management systems and paper-based document storage pose challenges to the institution’s management environment. To address these issues, the study aims to develop logical and management procedures using the object-oriented approach and create a web-based system. The System Development Life Cycle (SDLC) methodology is followed to ensure systematic development and meet all system requirements. Using Flutter and Firebase technologies, a standalone online system is constructed to streamline record management processes. This system improves accessibility, accuracy, and security of records, reducing reliance on manual paperwork. The application-based system enables efficient data storage, retrieval, and management, enhancing the overall learning experience and administrative efficiency. This study provides a foundation for similar initiatives in other educational institutions, leading to improved educational management practices through the integration of technology.